Stakeholder perception on implementation of public E-procurement in Kenya - Nyangaresi, Esther Njeri (Strathmore University, 2016)
The Kenyan e-procurement system, also known as integrated financial management information system (IFMIS) is an automated procurement system and a core component of public financial reforms in Kenya. It is used for public financial management and control, accounting, audit and reporting (Diamond & Pokar, 2005). It was first implemented in Kenya in 2013. The e-procurement system has been implemented in the ministries, departments, agencies and 47 county governments. The e-procurement system has automated supplier Management, Requisition Management, Quotation & Tender Management, Contract Management, Order Management, Inventory Management, Receipting Management, Invoice and Payment Management; online approval hierarchy for Purchase Order and Accounts Payable and automation of procurement planning in line with the approved budget estimates. This study sought to evaluate the stakeholder perception on implementation of e-procurement implementation by the Kenya government. The evaluation included identification and ranking of critical success factors and challenges that impede successful implementation of e-procurement in the Kenya government. Data was collected through a questionnaire that was distributed to procurement managers in both the government ministries and parastatals, and select government suppliers. The data was analyzed using descriptive statistics of percentages, means, standard deviations and frequencies. Content analysis was used to analyze the qualitative data. In addition, the study applied inferential statistics including multiple regressions and test of hypothesis to establish the relationship between identified and ranked critical success factors and success in implementation of e-procurement by the Kenya government. The study rated as moderate, the success of implementation of IFMIS e-procurement by the Kenya government. Capacity building, system integration, IT infrastructure and leadership were identified as critical in successful implementation of e – procurement system by the Kenya government. Poor training, inadequate information technology, (IT) infrastructure for the system, lack of technical expertise and inadequate awareness about the system have been identified as the greatest impediments to the success in implementing IFMIS e-procurement by the Kenya government. The study recommends among other things that, the government invest more in capacity building particularly investing in installation of the right IT infrastructure as well as training on using the system effectively. This study will be useful to the Kenya government in making e-procurement policies aimed at not only enhancing the success rate, but also addressing the challenges that impede the successful implementation of e-procurement.
Submitted in partial fulfilment of the requirements for the Degree of Master of Commerce (Forensic Accounting) at Strathmore University
Keywords: Stakeholder perception; Public E-procurement; Kenya; Integrated Financial Management Information system (IFMIS)